The Effect of Free and Back Swimming Practice on Rehabilitation of Thickness of the Rectus Abdominis Muscle, Erectus Spondylosis and Chronic Lower Back Pain for Ages (35-45) Years - Raheem, Majid Mohammed Ameen; Saadi, Ali Hasan Neamah (International Journal of Psychosocial Rehabilitation, 2020)
Abstract--The researchers pointed to the clear and influential role offered by exercising in general and swimming in particular in treating and rehabilitating many diseases and injuries in most of the developed world. Computer for long hours, wrong sitting, lack of movement, and lack of exercise in sports that leads to weak muscles surrounding the spine, which is the reason for back pain, so the researchers decided to study this problem by setting two qualifying programs to practice free swimming And the back to qualify this injury and reduce the chronic pain of the lower back and know which two types of swimming have the advantage in the rehabilitation. The study objective to:• Preparation of two qualifying programs for the practice of free and back swimming in the rehabilitation of the thickness of the rectus abdominis muscle, the erectus spondylosis, and chronic low back pain for ages (35-45) years.• Identify the effect of free swimming practice in rehabilitating the thickness of the rectus abdominis muscle, spondylitis, and chronic lower back pain for ages (35-45) years for the first experimental group.• Identifying the effect of back swimming practice on rehabilitating the thickness of the rectus abdominis muscle, spondylitis, and chronic low back pain for ages (35-45) years for the second experimental group.• Recognizing the preference of the effect of free and back swimming practice in qualifying the thickness of the rectus abdominis muscle, spondylitis, and chronic lower back pain for ages (35-45) years between the two experimental groups.The researcher used the experimental approach, and the research community identified from the employees of the University of Karbala the patients who suffer from chronic low back pain of (26) employees. Therefore, the sample selection came by intentional method by (10) employees and they were divided equally into two experimental groups, each group consisting of (5) Individuals who can swim free and back.